Pengolahan Limbah Minyak Pelumas dengan Menggunakan Metode Elektrokoagulasi - Lailan Ni'mah; Fauzan Fyanidah; Muhammad Danan Maulana (Universitas Ahmad Dahlan, 2017)
Most of users of lubricants are motor vehicles plus lubricating oil used for factory machinery. The amount of lubricating oil used will produce waste. Waste generated by the lubricant is included in the B3 waste which needs special handling. In this study used electrocoagulation because this method is easy and not too dangerous because there is no addition of chemicals. The objective of this study was to study electrocoagulation method using aluminum and steinless steel electrodes and the effect of time to decrease of Fe metal content. This electrocoagulation treats lubricating oil waste electrically so that the ions present in the waste are absorbed by the binding coagulant that is released electrode so that there will be bonds between metal ions with coagulant. The first reactor penetration procedure is filled with a lubricating oil waste containing Fe up to 1000mL. The anode (aluminum) is connected to the positive pole, whereas the cathode (stainless steel) is connected to the negative pole of the current rectifier (adapter). Voltage variations used are 12 volts, 18 volts and 24 volts and 5A current strength with stirring duration of each variation for 2 hours, 2.5 hours and 3 hours. Electrocoagulation result with 24 volt voltage with time of 3 hours for big plate is 26,44 is decrease of Fe content of biggest metal.